PKM Remaja Sehat Bersama SADARI di SMK Baiturrahim Jambi - Nurfitriani Nurfitriani; Hesty Hesty (Jurnal Abdimas Kesehatan (JAK), 2022)
Adolescence is a period of transition from childhood to adulthood where the breast organs begin to grow and develop rapidly so that they require optimal care such as breast self-examination (BSE). BSE is an early screening tool for breast cancer that can be done by a woman herself by touching and massaging around the breast, starting from adolescence with the hope that if a breast abnormality occurs, it can be treated early so that it can reduce the morbidity and mortality rate of women due to breast cancer. The purpose of this service is for students at Baiturrahim Vocational School to gain knowledge about BSE and be able to do BSE examinations themselves. Baiturrahim Vocational School was chosen as the location for community service, because it has a Nursing and Pharmacy study program and the majority (90%) are female. The results showed that 80% of Baiturrahim Vocational High School students participated in the activity with enthusiasm and appreciation and were interested in learning BSE and it is hoped that this counseling aterial can be applied to students and the surrounding community.